Software-Defined Radio FPGA Cores: Building towards a Domain-Specific Language. (17th July 2017) - Tsoeunyane, Lekhobola; Winberg, Simon; Inggs, Michael
Abstract : This paper reports on the design and implementation of an open-source library of parameterizable and reusable Hardware Description Language (HDL) Intellectual Property (IP) cores designed for the development of Software-Defined Radio (SDR) applications that are deployed on FPGA-based reconfigurable computing platforms. The library comprises a set of cores that were chosen, together with their parameters and interfacing schemas, based on recommendations from industry and academic SDR experts. The operation of the SDR cores is first validated and then benchmarked against two other cores libraries of a similar type to show that our cores do not take much more logic elements than existing cores and that they support a comparable maximum clock speed. Finally, we propose our design for a Domain-Specific Language (DSL) and supporting tool-flow, which we are in the process of building using our SDR library and the Delite DSL framework. We intend to take this DSL and supporting framework further to provide a rapid prototyping system for SDR application development to programmers not experienced in HDL coding. We conclude with a summary of the main characteristics of our SDR library and reflect on how our DSL tool-flow could assist other developers working in SDR field.